(untitled) (International Journal of Psychosocial Rehabilitation, 2021)
The word leverage refers to an increased means of accomplishing some purpose. Leverage is used to lift heavy objects, which may not be otherwise possible. In financial management, leverage refers to the ability to use fixed-cost assets or funds to increase the return to its shareholders. According to James Horne, “the employment of an asset or fund for which the firm pays a fixed cost or fixed return.”. Leverages results as results of an organization employing an asset that has a fixed cost. In this study, the leverages of Hindustan Unilever Limited have been studied to know the impact of leverages on the financial status of the company.